VD_FINDINFO Réc-civile / 2017 / 17 vom 28. August 2014 - VD Tribunal cantonal (2014)
AUTORITÉ DE RECOURS, PLACEMENT À DES FINS D'ASSISTANCE, EXPERTISE, FRAIS JUDICIAIRES | 450e al. 3 CC, 28 TFJC, 106 al. 1 CPC (CH), 47 al. 1 let. b CPC (CH), 47 al. 1 let. f CPC (CH), 50 al. 2 CPC (CH), 8a al. 7 CDPJ